Pengaruh Displin Kerja, Fasilitas Kerja dan Promosi Jabatan Terhadap Kinerja Karyawan (Studi Kasus Industri Manufaktur di Jakarta ) - Wulan, Nawang; Tarmizi, Achmad (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
This study aims to evaluate the influence of work discipline, workplace facilities, and job promotion on the performance awareness of companies in the manufacturing sector in Jakarta. In this research, a quantitative method will be employed using a saturation sampling technique, where the entire population will be included with the participation of 60 respondents. Data will be collected using IBM SPSS Statistic Version 26 software. The results of the study indicate that there is a significant positive influence of work discipline and workplace facilities on employee performance partially. However, job promotion does not have a significant influence on employee performance partially. Overall, work discipline, workplace facilities, and job promotion together have a positive and significant impact on employee performance. The implications of these findings highlight the importance of performance in the context of companies to enhance the effectiveness and efficiency of human resources. This research contributes originality by exploring work discipline, workplace facilities, and job promotion as independent variables affecting company performance as the dependent variable, which is a new addition to research literature.